Modeling and performance analysis of open-loop remotely operated vehicles ORCA - Panati, Tejaswini; Indraganti, Sai Deepika; Santhanam, Sakthivel Murugan (IAES International Journal of Robotics and Automation (IJRA), 2023)
ORCA is a low cost remotely operated vehicle which was indigenously developed for underwater inspection and survey. As the underwater environment is quite unpredictable, dynamic modeling and simulation of the remotely operated vehicle are essential to understand the behavior of the vehicle and accomplish stabilized navigation. This paper discusses a detailed approach to the mathematical modeling of ORCA based on Newtonian dynamics and simulating the position and velocity responses in Simulink. The open loop nonlinear model of the remotely operated vehicle was used to study the navigation challenges due to the various perturbations present underwater namely Coriolis and centripetal force, added mass, hydrodynamic damping force, and restoring forces. The six-thruster open loop ORCA model was subjected to various thrust inputs (25%, 50%, and 75%) to achieve six degrees of freedom (DoF) respectively and it was observed that there was significant instability in the other DOFs along with the principal direction of motion. Further, the authors will incorporate the various control systems in ORCA and analyze the stability in navigation induced due to each of them.